The Role of Technical English Language on Modern Engineering Education - Minoo Alemi (آموزش مهندسی ایران, 2016)
In classical and modern fields of engineering such as electrical, mechanical, electronics, information technology, telecommunications, mechatronics, computer science, robotics, artificial intelligence, cognitive, etc., technical English language has been well accepted as a common language of communication for written diffusion of subjects and oral presentations at international conferences (especially in non-English developing countries). On the other hand, with increasing labor mobility in the global village engineers need to improve and enhance their communication skills on the international scale which is crucial and considered as a sign of excellence. These skills not only include the main purposes from the linguistics point-of-view, such as improving pronunciation, better command of vocabulary, etc., but also include social and cultural skills as well as the ability to use different strategies or compensation communication (like interpreting) when verbal meanings seem insufficient. The authors in this paper first examine the role and impact of Technical English in modern engineering education, and then will discuss the basic features of communication skills that need to be included in undergraduate engineering curricula.